ASSOCIATION OF DEGREE OF ST SEGMENT DEPRESSION WITH IN-HOSPITAL MORTALITY IN PATIENTS WITH NON-ST ELEVATION MYOCARDIAL - Awan, Muhammad Saleem; Daud, Muhammad Yousuf; Khan, Matiullah; Jehangiri, Attique Ur Rehman; Ali, Rashid; Jalil, Shaista (Journal of Ayub Medical College Abbottabad, 2018)
Background: Ischemic heart disease is responsible for approximately 1/3 of all global deaths, making it a leading cause of cardiovascular mortality. Non-ST-segment elevation acute coronary syndrome (NSTE-ACS) which is an acute event in spectrum of coronary artery disease, is a potentially life-threatening emergency, makes up for the majority of admissions to a cardiac unit with one-year mortality rate of 23.5%. The objective of this study was to determine the association of degree of ST segment depression on hospital mortality in patients presenting with Non-ST segment elevation myocardial infarction (NSTEMI). Methods: This descriptive case-series was carried out in the department of Cardiology, Punjab Institute of Cardiology Lahore. Using Non-probability purposive sampling technique, a total of 250 patients of age between 30-75 years of either gender, who reported during the study period, with NSTEMI were inducted in this study. Results: In our study, 33.2% (n=83) patients were between 30-50 years and 66.8% (n=167) patients were between 51-75 years of the age. Mean age was 54.64±9.69 years. 43.2% (n=108) patients were male and 56.8% (n=142) were females. Frequency of in-hospital mortality was 4.4% (n=11). Mortality increased with increasing degree of ST segment depression on admission Electrocardiogram (ECG). Conclusion: In patients admitted with Non-ST segment elevation myocardial infarction (NSTEMI), degree of ST segment depression on admission ECG predicts In-Hospital mortality. Keywords: Non-ST segment elevation myocardial infarction (NSTEMI); ST-segment depression; in-hospital mortality